PRODUCT DEVELOPMENT STRATEGY FOR FARMER GROUPS IN THE DIGITAL ERA BASED ON URBAN FARMING IN CIOMAS RAHAYU VILLAGE - Sri Hidajati Ramdani; Tutus Rully; Eka Patra; Yohanes Indrayono (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
Ciomas Rahayu Village is one of the villages located in Bogor Regency and has area of 88.450 ha. However, 70% of the land in this village is used for residential needs, resulting in a lack of vacant lang, wich necessitates the implementation of the urban farming in the Farmer Groups (Poktan) and Woman Farmer Groups (KWT) to utilize the remaining land productive. Ciomas Rahayu Village has 5 Poktan dan 1 KWT that produce organic vegetables and organic freshwater fish. Seeing the opportunity to develop products from Poktan and KWT, this research aims to formulate an alternative product development strategy by adjusting to technological developments and describing the factors that need to be considered in Ciomas Rahayu Village. This research is descriptive with qualitative approach. The sampling method used was purposive sampling. The data obtained were analyzed using SWOT analysis. The result show that the alternative strategies generated are implementing product development to increase the product's value added and quality, and implementing digital marketing to reach a wider market.